Coexistence of phases in asymmetric nuclear matter under strong magnetic fields - Aguirre, Ricardo Miguel (2015)
The equation of state of nuclear matter is strongly affected by the presence of a magnetic field. Here we study the equilibrium configuration of asymmetric nuclear matter for a wide range of densities, isospin composition, temperatures and magnetic fields. Special attention is paid to the low density and low temperature domain, where a thermodynamical instability exists. Neglecting fluctuations of the Coulomb force, a coexistence of phases is found under such conditions, even for extreme magnetic intensities. We describe the nuclear interaction by using the non-relativistic Skyrme potential model within a Hartree-Fock approach. We found that the coexistence of phases modifies the equilibrium configuration, masking most of the manifestations of the spin polarized matter. However, the compressibility and the magnetic susceptibility show clear signals of this fact. Thermal effects are significative for both quantities, mainly out of the coexistence region.